System design of video surveillance - Mohanad Abdulhamid; Mwongeera Murungi (Sistemnì Doslìdženâ ta Informacìjnì Tehnologìï, 2019)
This paper describes the steps involved in designing of a video surveillance system. It discusses the theory of video surveillance types, components involved, selection of the best equipment, and also a detailed virtual design. An introduction of the concept of video surveillance systems is followed by the detailed discussion of design considerations and the design verification. The system is designed to monitor a bank floor where the monitor displays the desired output from a simulated implementation of the system.